Peran Badan Kemanan Laut Republik Indonesia Stasiun Sambas Dalam Pengawasan Wilayah Laut Perbatasan Indonesia-Malaysia di Kalimantan Barat - Widianti, Anyta; Wijaya, Budi; Yanti, Murny Deni; Mutia, Mutia; Marsela, Selly (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This research analyzes the role of the Indonesian Maritime Security Agency (Bakamla RI) in monitoring the Indonesia-Malaysia border maritime area in West Kalimantan based on in-depth interviews with Bakamla personnel at Sambas Station. This study integrates primary and secondary data to understand the mechanisms of monitoring, patrolling, and inter-agency coordination. The results show that Bakamla plays a significant role in early detection and security patrols, but still faces obstacles such as limited fleet, operational area size, and budget constraints. The study recommends increasing operational capacity, harmonizing regulations, and optimizing budgets to strengthen Bakamla's function in the border region.